PERAN OPSEN PAJAK DALAM REFORMASI FISKAL NASIONAL - Suprihatno, Andri; Prayogi, Prayogi; Sidiq, Gifar Fajar; Nasrullah, Nasrullah; Najmudin, Nandang (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
National fiscal reform is a strategic step by the government in strengthening regional fiscal independence and improving the structure of state revenues. This national fiscal reform aims to create a fairer, more transparent and sustainable state financial system. One of the key instruments in this reform is the implementation of tax options, namely additional levies on certain taxes whose results are shared between the provincial and district or city governments, in this context, tax options (additional tax levy options that have been set by the central government) become an important instrument to increase regional funding capacity without creating new types of taxes. Tax options play a strategic role in strengthening regional fiscal independence without adding new tax burdens to the community. This article discusses the role of tax options in encouraging fiscal decentralization, increasing the efficiency of regional tax revenues, and strengthening synergy between the central and regional governments. This writing uses a qualitative descriptive approach with an analysis of fiscal policy and the latest regulatory framework. The results of the study show that the implementation of tax options, if supported by a transparent distribution and supervision system, can expand regional fiscal space while maintaining national fiscal stability.